Effects of aqueous ozone pasteurization on S. typhimurium inactivation and qualitative attributes of chokanan mango (Mangifera indica L.) fruit juice - Mohd Supian, Nur Amira (2021)
The juice and beverages industry shows rapid growth from year to year in line with the rise of fruits consumption. The consumers tend to add fresh fruit juice to supplement their healthy lifestyle and these choices include nutrient-rich mango fruit of Chokanan variety. Nonetheless, the risk of cross-contamination of fresh fruits are increasing as the import volume from other countries are also amplifying. The risk may exacerbate if the hygiene practice of the fruit juice handlers is abysmal. Secondary preservation methods to produce safe fruit juice is imperative as S. typhimurium contamination of mango juice could potentially cause severe harm to consumers since this pathogen can attach and infiltrate the mango fruit. Even though the thermal pasteurization method has been proven effective towards microorganism inactivation, the treatment can affect the nutritional quality of mango juices (MJ). Thus, the juice industry and academia are actively investigating alternative pasteurization technologies and ozone is one of the novel technologies attracting their interests because it does not leave any undesirable residue in the treated food product in addition to its ability to destroy harmful pathogens. However, it is challenging to predict ozone’s antimicrobial behaviour in fruit juices as it depends not only on the ozone processing parameters (processing time and ozone dose) but also on the treated juice composition. Hence, this study was done to evaluate the efficiency of ozone as a substitute pasteurization method to thermal treatment towards S. typhimurium inactivation and retention of physicochemical and antioxidant properties of various concentration ratios of Chokanan mango juice diluted with distilled water (DW); 100MJ:0DW, 75MJ:25DW, and 50MJ:50DW. The abovementioned mango juice samples were then treated to ozone treatment with ozone doses of 0.33, 0.67, 1.00, and 1.33 mg/mL for 10, 20, 30, and 40 min. The results from this study have shown that the efficacy of ozone pasteurization is significantly (p < 0.05) affected by mango juice concentration ratios; where it can be seen that the inactivation rates for 5-log reduction of S. typhimurium was observed at 36.39 min, 1.20 mg/mL (for sample 100MJ:0DW), 28.38 min, 0.95 mg/mL (for sample 75MJ:25DW) and 24.82 min, 0.82 mg/mL (for sample 50MJ:50DW). In addition to that, the inactivation of S. typhimurium in MJ samples has successfully achieved the 5-log reduction within 40 min (at ozone dose of 1.33 mg/mL) and 30 min (at ozone dose of 0.33 mg/mL) and these results fitted well to the Weibull model. This study also offers some insight into the effects of ozone on the quality attribute of MJ samples. The results showed significant changes (p < 0.05) in the pH and total soluble solids (TSS) value of MJ samples. Ozone was found to be effective in lowering the pectin methylesterase (PME) activity (p < 0.05) from de-esterifying the pectin molecules and increased (p < 0.05) the DPPH activity of MJ samples, thereby increasing the juice's quality. However, a significant decrease (p < 0.05) was seen in the total color difference (TCD), ascorbic acid, and total phenolic content (TPC) on ozone-treated MJ samples. Therefore, to further support physicochemical analysis findings, colour kinetic was studied to predict mango fruit juice's quality degradation due to ozone treatment. The first-order reaction model was shown to best fit the color L*, b*, and TCD values. A significant difference (p < 0.05) can be observed between the degradation rate constant (k-value) for all MJ samples, which implies that the k-value is not only affected by ozone dose but also by juice’s matrix. The 50MJ:50DW sample also shows the lowest percentage changes in color (b*) value and kTCD degradation corresponds to juice composition. In summary, the results of this study proved that aqueous ozone can potentially be used as pasteurization method in juice processing; where it can reduce S. typhimurium by 5-log reduction and managed to minimize the nutrient content changes in MJ samples. Nevertheless, it is imperative to examine the juice composition as a crucial intrinsic parameter in order to gauge the efficacy of juice preservation perusing ozone technology.